Stress-induced electrolyte leakage from root cells of higher plants: background, mechanism and physiological role - Hryvusevich, Palina V.; Samokhina, Veranika V.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2022)
Electrolyte leakage from tissues is one of the central reactions of the plant organism to stress. It is observed under almost any type of stresses, both abiotic and biotic. The loss of key electrolytes can lead to significant changes in metabolism and, in some cases, to the death of cells or the whole organism. For a long time, it was believed, that electrolyte leakage is associated with disruption of cell integrity and plasma membranes degradation, and that it is an unregulated process. However, in recent years, a lot of evidence has been received that, in most cases, electrolyte leakage is inhibited by ion channel blockers and reversible. It means that it is associated with the transfer of ions through the membrane by transport proteins, such as ion channels. Recently, the experimental evidence has been obtained, that under salinity, drought, pathogen attack, excessive levels of heavy metals, hypo- and hyperthermia, as well as oxidative stress, the electrolyte leakage in plant cells is mediated by several types of cation and anion channels, including K+-selective channels (SKOR and GORK), anion channels (such as ALMT1) and a number of non-selective cation channels. It has been demonstrated that the primary reactions that induce electrolyte leakage are plasma membrane depolarisation and generation of reactive oxygen species, leading to the activation of redox-regulated outwardly rectifying K+ channels, such as SKOR and GORK. Potassium efflux is up-stream and stimulates the counterion flow (transport of anions) through the anion channels. The regulation of electrolyte leakage at the ion channel level and the corresponding selection for ion channel properties can become an important link in the directed control of stress resistance in higher plants. This can be applied in agriculture via breeding of stress-tolerant plant varieties, as well as developing modern amelioration techniques.